3D graphene foam-reinforced polymer composites – A review. (August 2018) - Idowu, Adeyinka; Boesl, Benjamin; Agarwal, Arvind
Abstract: This review summarizes the present state and advances of three-dimensional (3D) graphene foam-reinforced polymer matrix composites (GrF-PMC). Graphene foam as a filler is being considered to address challenging issues of graphene dispersion and restacking in composite materials because of its three-dimensional interconnected hierarchical structure and its physio-chemical attributes. Synthesis approaches to prepare 3D graphene-based frameworks, node-branch behavior and intrinsic material properties of free-standing graphene foam are highlighted. The review discusses different processing techniques to fabricate graphene foam-based polymer composites which can be employed in structural and thermal applications. Influence of graphene foam addition on the mechanical behavior of GrF-PMC has been critically examined. Additionally, the electrical, thermal and other material properties vested in graphene foam to enhance the multifunctional behavior of GrF-PMC are summarized. Current challenges associated with GrF-PMC are discussed, and research pathway into the future for progress in GrF-PMC are introduced. Graphical abstract: Image 1